Answer: You want to use in this problem is the distributive property of multiplication.
Step 1: Distribute 1/9 or multiply 1/9 by 2m and -16m, then do the same to the other side of the equation only this time you are distributing 1/3
1/9(2m-16) = 1/3(2m+4)
2/9m -16/9 = 2/3m+4/3
Step 2: Since you have a variable in each side of the equation what you want to do is subtract the smallest of the two variables becasue they are like terms. This way you'll get rid of one of your varibles so you can solve for m. So you would subtract 2/9m from 2/3m because 2/9 is smaller.
2/9m -16/9 = 2/3m +4/3
-2/9m - 2/9m
-16 /9 = 4/9m +4/3
Step 3: Now subtract 4/3 from each side because you want to solve for m
-16/9 = 4/9+4/3
Step 4: Now divide by 2/3 in order to solve for m, but rememeber that when you are dividing by a fraction you have to invert it or flip it around.
-28/9 = 2/3m
-28/+9 x 3/2 = 2/3m x 3/2
-28/6 = m
reduce : -14/3 = m